Bone disease in patients with chronic kidney disease under conservative management - Gomes, Carlos Perez; Silva, Maria Inês Barreto; Duarte, Maria Eugênia Leite; Dorigo, David; Lemos, Carla Cavalheiro da Silva; Bregman, Rachel (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Few studies have focused on bone disease in patients with chronic kidney disease under conservative treatment. The objective was to evaluate bone disease in patients with chronic kidney disease. DESIGN AND SETTING: Case series, at the Nephrology Division, Hospital Universitário Pedro Ernesto. METHODS: 131 patients with creatinine clear- ance from 10 to 60 ml/min/1.73 m² were fol- lowed up for at least one year. Serum creatinine, albumin, calcium, phosphorus, alkaline phos- phatase, total CO2 (tCO2), intact parathyroid hormone (iPTH), and alkaline phosphatase were measured. Creatinine clearance was calculated from 24-hour urine creatinine measurements and protein ingestion estimates from urea assays. RESULTS: Patients presenting creatinine clearance < 30 ml/min/1.73 m² had higher iPTH values, but normal serum levels for calcium, phosphorus, alkaline phosphatase and tCO2. Patients present- ing iPTH values of twice the normal upper limit (144 pg/ml) showed lower tCO2 values. Bone al- kaline phosphatase was evaluated in 37 patients with creatinine clearance < 30 ml/min/1.73 m², showing correlation with alkaline phosphatase but not with parathyroid hormone. Bone biopsy on nine patients with creatinine clearance < 30 ml/min/1.73 m² and iPTH > 144 pg/ml showed osteitis ﬁbrosa (4), mild lesion (4) and high turnover (1). CONCLUSION: The present data suggest the importance of early control for iPTH and metabolic acidosis, among patients under conservative management for chronic kidney disease, in order to prevent complications related to bone disease.